Sustainable supply chain in the cement sectors: Implications for environmental policy and education in Indonesia - Sodik, Aris; Cahyadi, Eko Ruddy; Mulyati, Heti (Journal of Environment and Sustainability Education, 2025)
Implementation of Sustainable Supply Chain Management (SSCM) is crucial for cement manufacturers to enhance competitive advantage while minimizing economic, social, and environmental impacts. As a result, cement companies must assess, manage, and report the sustainability performance of their supply chains. However, there is no appropriate measurement framework to evaluate SSCM performance. This study designs a specific and relevant SSCM performance measurement framework, referring to global cement industry indicators, empirical indicators of Indonesian manufacturers, and validation of seven cement supply chain specialists. A systematic literature search was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method, and the Analytical Hierarchy Process (AHP) was used to assign weights to performance indicators. This study develops an SSCM framework that integrates three aspects of sustainability: environmental, social, and economic. The framework consists of 22 performance indicators, including six environmental indicators, eight social indicators, and eight economic indicators. Testing the framework on leading cement company in Indonesia resulted in a strong performance score of 80.7. This study addresses the existing gap in research related to supply chain sustainability and, for the first time, provides locally developed SSCM performance indicators that are aligned with the context of the Indonesian cement industry. This study also discusses the implications of the developed SSCM framework for sustainability education and capacity building within the Indonesian cement industry, highlighting the importance of integrating environmental, social, and economic performance indicators into training programs and educational curricula to foster sustainable business practices.